PENGARUH INTENSITAS MODAL, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Lestari, Lestari; Dewi, Eka Kusuma (JURNAL AKUNTANSI BARELANG, 2024)
ABSTRACTThis study aims to obtain empirical evidence about the effect of capital intensity, sales growth, and company size on tax avoidance. This type of research uses quantitative research using secondary data in the form of company annual reports taken from the energy sector listed on the Indonesia Stock Exchange for the period 2018 to 2022. The sampling method uses purposive sampling. The sample contained in this study was 75 data. Researchers used panel data regression techniques to test the research data using eviews 12 as a statistical tool. The results of data analysis show that simultaneously capital intensity, sales growth, and company size affect tax avoidance. Partially, the results showed that capital intensity and company size have no effect on tax avoidance, while sales growth has an influence on tax avoidance.